A Microfluidic Impedance Cytometer on Printed Circuit Board for Low Cost Diagnosis - Guo, Jinhong (2016)
Coulter counters have been an important platform in biological cell detection and enumeration for several decades. Recently, the portable Coulter counter has attracted much attention due to its advantages in point of care diagnostics for on chip detection and enumeration of rare cells, such as circulating tumor cells. In this paper, we present a microfluidic cytometer based on Coulter principle on a SU-8 coated printed circuit board (PCB) substrate, which enables portable and low-cost diagnostics. The electrical current changes induced by the blockage of the microparticles in the sensing aperture of the Coulter counter are numerically analyzed and validated by experimental studies. Hela cells are used to test the performance of the proposed device. The proposed cytometer is built upon the cheap and widely available PCB substrate and show its great potential as a personalized healthcare monitor.